CircHECTD1 mediates pulmonary fibroblast activation via HECTD1. (November 2019) - Chu, Han; Wang, Wei; Luo, Wei; Zhang, Wei; Cheng, Yusi; Huang, Jie; Wang, Jing; Dai, Xiaoniu; Fang, Shencun; Chao, Jie
Background: Circular RNA (circRNA), a new class of noncoding RNA, has been shown to be important in silicosis due to its unique role as a transcription regulator or as a sponge of small RNA regulators. Here, the mechanisms underlying circHECTD1/HECTD1 in fibroblast activation and subsequent fibrosis induced by SiO2 were investigated. Methods: Primary human pulmonary fibroblasts (HPF-a) were utilized, combined with quantitative real-time PCR (qRT-PCR) and fluorescence in situ hybridization (FISH) assays. LC3B-LV-RFP lentivirus was used to evaluate the role of autophagy. The CRISPR/Cas9 system was applied to specifically knock down HECTD1, combined with MTT, BrdU, and migration assays, to explore the functional changes induced by SiO2 . Results: After exposure to SiO2, the circHECTD1 level was decreased, which was associated with an increase in HECTD1 in HPF-a cells. SiO2 -induced autophagy was reversed by either circHECTD1 overexpression or HECTD1 knockdown in HPF-a cells, with restored SiO2 -induced fibroblast activation, proliferation, and migration via downstream autophagy. The lungs of mice exposed to SiO2 confirmed the upregulation of HECTD1 in pulmonary fibroblasts. Conclusions: Our data suggested a link between circHECTD1/HECTD1 and fibroblast activation with subsequent fibrosis induced by SiO2, providing novel insight into the potential of circHECTD1/HECTD1 to be a therapeutic target for silicosis.